2015
DOI: 10.1186/s40529-015-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and mechanisms of Salvia sclarea essential oil

Abstract: BackgroundNowadays, essential oils are recognized as safe substances and can be used as antibacterial additives. Salvia sclarea is one of the most important aromatic plants cultivated world-wide as a source of essential oils. In addition to being flavoring foods, Salvia sclarea essential oil can also act as antimicrobials and preservatives against food spoilage. Understanding more about the antibacterial performance and possible mechanism of Salvia sclarea essential oil will be helpful for its application in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 31 publications
(32 reference statements)
2
67
0
4
Order By: Relevance
“…Cui et al . () reported that Salvia sclarea EO, which contain 74·56% linalyl acetate and 13·26% linalool, decreased E. coli DNA by 50·77%. Regarding EO components, carvacrol and 1,8‐cineole; or combinations of 1,8‐cineole‐linalool or 1,8‐cineole‐ α ‐terpineol led to alteration of the cell wall structure and to the release of constituents including DNA (de Sousa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Cui et al . () reported that Salvia sclarea EO, which contain 74·56% linalyl acetate and 13·26% linalool, decreased E. coli DNA by 50·77%. Regarding EO components, carvacrol and 1,8‐cineole; or combinations of 1,8‐cineole‐linalool or 1,8‐cineole‐ α ‐terpineol led to alteration of the cell wall structure and to the release of constituents including DNA (de Sousa et al .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the zones of inhibition for P. aeruginosa and E. coli were 20 and 25 mm, respectively [126]. A study by Cui et al [69] has shown that Salvia sclarea oil showed a considerable inhibitory potential against the growth of E. coli, S. aureus, Bacillus pumilus, K. pneumoniae, B. subtilis, S. typhimurium, and P. aeruginosa with MIC and MBC of 0.05 and 0.1%, respectively. Ahmadi et al [77] reported the antibacterial properties of Thymus kotschyanus essential oil against B. cereus , E. coli, S. aureus , and S. epidermidis.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Furthermore, MIC /2 concentration of T. daenensis and O. vulgare EOs caused a significant downregulation of efflux pump gene (pmrA) in seven of eight strains. A further confirmation of the potential plural mode of action of the EO come from a study on Salvia sclarea EO on seven pathogens bacterial strains: it seems that the antimicrobial way of action involves a series of events both on the cell surface and within the cytoplasm . Many concerns are directed to bacterial species capable of forming biofilms, an aggravating factor for the difficult eradication of the bacterial colonization in surfaces (especially in the hospitals and food industries) and human organs (lung for example).…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…A further confirmation of the potential plural mode of action of the EO come from a study on Salvia sclarea EO on seven pathogens bacterial strains: it seems that the antimicrobial way of action involves a series of events both on the cell surface and within the cytoplasm. [288] Many concerns are directed to bacterial species capable of forming biofilms, an aggravating factor for the difficult eradication of the bacterial colonization in surfaces (especially in the hospitals and food industries) and human organs (lung for example). Prevention of biofilm formation and anti pre-formed biofilm activity of oregano essential oils was evaluated mainly against Staphylococcus aureus and Pseudomonas aeruginosa, [289,290] with the result that the tested EOs are active in preventing biofilm formation and are effective agents to remove young and mature S. aureus biofilms on stainless steel surfaces.…”
Section: Antimicrobial Activitymentioning
confidence: 99%